PH-Sensitive fluorophores from locked GFP chromophores by a non-alternant analogue of the photochemical meta effect. Issue 38 (16th September 2016) - Olsen, Seth; Baranov, Mikhail S.; Baleeva, Nadezhda S.; Antonova, Maria M.; Johnson, Kenneth A.; Solntsev, Kyril M.
Abstract : We report the synthesis and characterization of a pH-sensitive fluorescence switch based on a conformationally-locked green fluorescent protein (GFP) chromophore. Abstract : We report the synthesis and characterization of a pH-sensitive fluorescence switch based on a conformationally-locked green fluorescent protein (GFP) chromophore. The chromophore differs from difluoroboryl-locked parent by the addition of a titratable alcohol group on the imidazolinone ring. The chromophore is fluorescent at pH ≤ 5, but becomes non-fluorescent at higher pH, where the substituent is ionized. We use a quantum chemical model to show that the mechanism of the fluorescence turn-off is electronically analogous to photochemical meta effects in aryl-containing systems.